Training and Development - Enhancing Employee Performance - Alhowaish, Jawaher Ali (Journal of Global Economy, Business and Finance, 2024)
The purpose of this study was to how beneficial of training and development programs on employee performance for organisation development. Training and development programs typically involve educational activities that advance a worker’s knowledge and ignite greater motivation to enhance job performance. The study also reveals that training and development is a necessity in every company/organisation particularly for the unskilled, semiskilled, newly inducted or the less experience employees. Generally, employees’ work contribution was greatly improved due to the different training methods and tools used by the company. Thus, it led to a positive impact on the overall employee’s performance and an improvement in their skills and job efficiency. There are many types of training and development. Benefits of employee training and development like Increased productivity. At present Remote mobile training and AI training are passionate now a days and modern gadgets are useful to give training without physical participation.